The new outlawry and Foucault’s Panoptic nightmare - Russell, Steve (American journal of criminal justice, 1993)
Michel Foucault seized upon Bentham’s “Panopticon” prison design as a metaphor to illustrate the mechanisms of social control in post-industrial society. In our recent rush to invent alternatives to incarceration, we have created a new and burgeoning class of outlaws, persons for whom privacy is not a legally cognizable right. Combined with Supreme Court decisions finding surveillance of even innocent citizens to be constitutionally benign, our well-intentioned efforts to reduce prison populations are close to bringing Foucault’s metaphor to literal reality.